The Impact of Mathematical Thinking on Social Dynamics in 5th Grade Students through the Development of Problem Solving (Docentes 2.0 Journal, 2025)
The ability to solve mathematical problems efficiently is essential for mastering this area of ??knowledge. In addition, it is considered a transversal skill that influences cognitive development and decision-making in various areas of life. The study's objective was to evaluate the impact of a pedagogical strategy based on strengthening problem-solving skills on the development of mathematical thinking in 5th-grade students in Magangué, Colombia. The research was based on the inductive-deductive method, pragmatic paradigm, mixed approach, sequential design, nested concurrent dominant model, and longitudinal section. The sample consists of 210 students, divided into control and experimental groups, with 105 students in each group. Consequently, diagnostic instruments were designed to evaluate the development of mathematical thinking and problem-solving skills before and after implementing the pedagogical strategy. In this order of ideas, it was determined that the results obtained provided empirical evidence on the effectiveness of the pedagogical strategy in developing mathematical thinking in 5th-grade students in Magangué, Colombia. Likewise, it should be noted that this research contributed to the design of effective educational interventions that promote the comprehensive development of students, strengthen their cognitive skills, and improve their academic performance in mathematics.
Keywords: Mathematical thinking; problem solving; academic performance; , educational assessment; active learning